Improving the Quality of Public Services in the District Government of Kutai Kartanegara Regency (Analysis of Challenges and Opportunities in Welcoming the Presence of the New Capital City) - Daryono (Konsultan Surya Buanan, 2025)
Quality public services are the main foundation for realizing effective governance that is oriented towards the interests of the community. This study aims to analyze the quality and reform of public services in five sub-districts in Kutai Kartanegara Regency: Tenggarong Seberang, Kembang Janggut, Kenohan, Loa Janan, and Loa Kulu. The urgency of this research lies in the need to strengthen the accountability and professionalism of civil servants amidst public demands for fast, transparent, and technology-based services. Using a qualitative approach supported by quantitative data, this study examines the implementation of ethics, standards, principles, and supervision of public services through a survey of civil servants and the community. The results show that all sub-districts are in the good to very good category with an average score of 74–83%. Kenohan Sub-district obtained the highest score (83%) in the reform and supervision aspects, while Loa Kulu and Loa Janan showed the lowest scores, indicating the need to improve facilities and capacity of civil servants. This study emphasizes the importance of strengthening human resource capacity, digitizing services, and inter-agency collaboration to realize professional, accountable, and sustainable public services.